Effect Of Wax-Based Oleogel As Novel Frying Medium On Oxidative Stability And Anthocyanin Retention Of Purple Sweet Potato Chips - Azman, Noor Amira Syamimi Noor (Universiti Sains Malaysia, 2020)
Purple sweet potato (PSP) is rich in anthocyanin content that provide attractive purple color and nutritional benefits. However, the anthocyanin degrades during frying when exposed to high temperature. This study sought to study the effects of wax-based oleogel as frying medium on the anthocyanin retention, antioxidant activity and oil uptake of PSP chips. The pretreatment of PSP slices with citric acid (4%) soaking was studied at different time (1, 3 and 5 min) followed by superheated steam (SS) at 160 ˚C for 5 min. Subsequently, the pretreated PSP chips were fried in palm oil without (control) and with candelila wax (oleogel oil) and the anthocyanin and antioxidant retention as well as oil uptake were evaluated. The moisture sorption isotherms of the samples were determined and accelerated storage study of the packaged PSP chips in aluminium seal pouch was conducted for two weeks at 45 ˚C. Frying PSP chips with oleogel significantly increased anthocyanin content by 82% and reduced the oil uptake by 48% compared to the control sample. During storage, the anthocyanin content and lipid oxidation were maintained in the oleogel sample.